Ókori keleti történeti chrestomathia (2., verbesserte Auflage) (1986)
Chrestomathie zur Geschichte des Alten Orients; vgl. 27 c 95; S. 83-237 Mesopotamien (A.Dávid, G. Komoróczy), S. 239-252 Mitanni-Syrien-Phönizien (J. Harmatta, G. Komoróczy), S. 253-264 Hatti (J. Harmatta), S. 293-302 Urartu (J. Harmatta, G. Komoróczy), S